INTRODUKSI TEKNOLOGI PEMBUATAN WALL DECORATION MELALUI PELATIHAN WIRAUSAHA MANDIRI DI KOTA METRO - Nurul Farida; Lilian Mega Puri; Triani Ratnawuri (LPPM Universitas Andalas, 2020)
The activity aimed to provide training in making flannel wall decoration as a provision for independent entrepreneurship for Tuma'ninah Yasin youth orphanage. It makes flannel more attractive with a colorful appearance to make craft products that have a sale value. Another advantage of flannel is that it is affordable, making it possible to do entrepreneurship with small capital. Through this training on making flannel wall decoration, it is hoped that it can become a provision for teenagers' independent entrepreneurship at the Tuma'ninah Yasin orphanage, Metro City. The partners of this activity are teenagers at the Tuma'ninah Yasin orphanage, Metro City. The group of teenagers at the Tuma'ninah Yasin orphanage, Kota Metro, is a partner with the most active and productive teenagers. The Tuma'ninah Yasin orphanage has many young men and women who are active and productive, but they do not have the ability and skills to produce products that are worth selling. The venue for the training activities is at the Tuma'ninah Yasin Orphanage Mosque, Metro City. The methods used in this activity are demonstration, question and answer, discussion, and practice methods. The results of the activities obtained are that the training participants/partners can develop the manufacture of various kinds of handicrafts / handmade products from flannel to develop and become provisions for independent entrepreneurs. Based on the activity results, it can be concluded that 93% of the training participants have the knowledge and skills in making flannel wall decorations.